Crushed - Shepard, Sara, 1977- (New York, NY : HarperTeen, 2013)
The girls prepare for prom while trying to track down A.
Young Adult.
Young Adult
Keywords: Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Proms -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Fiction; Friendship -- Fiction; Mystery and detective stories; Proms -- Fiction; Secrecy -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Mystery fiction; Proms -- Fiction; Secrecy -- Fiction; Mystery fiction